Proceedings on Seventh International Conference on Information Visualization, 2003. IV 2003.
DOI: 10.1109/iv.2003.1218027
|View full text |Cite
|
Sign up to set email alerts
|

Movement as an aid to understanding graphs

Abstract: This paper describes a graph visualization method

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…The only challenge is to distinguish the distance distortion and cluster overlapping introduced by the mapping. Uniquely different from other models, by tuning α i values, we can scrutinize the multidimensional dataset visually from different perspectives, which gives dynamic visual clues for distinguishing the visual overlapping 2 . In addition, since this model is a record-based mapping function, it is naturally parallel and can be implemented with the popular parallel processing models such as MapReduce [7] for large scale cloud-based data processing.…”
Section: The Vista Visualization Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The only challenge is to distinguish the distance distortion and cluster overlapping introduced by the mapping. Uniquely different from other models, by tuning α i values, we can scrutinize the multidimensional dataset visually from different perspectives, which gives dynamic visual clues for distinguishing the visual overlapping 2 . In addition, since this model is a record-based mapping function, it is naturally parallel and can be implemented with the popular parallel processing models such as MapReduce [7] for large scale cloud-based data processing.…”
Section: The Vista Visualization Modelmentioning
confidence: 99%
“…The family of star coordinates systems [16,3] address the visual distortion problem with a more efficient way, which is also the basis of our approach. The advantage of stochastic animation in finding patterns, as we do with RandGen, is also explored in graph visualization [2] The three-phase framework "sampling or summarization -clustering/cluster analysis -disk labeling" is often used to incorporate the algorithms of high time complexity in exploring large datasets. As the size of data grows to very large, the rate between the size of the sampled or summarized dataset to the original size becomes very small, affecting the fidelity of the preserved clustering structure.…”
Section: Related Workmentioning
confidence: 99%
“…To motivate the subjects we decided to make the investigation part of a game that could only be played successfully by subjects who understood the structure of the displayed graph Whilst there is previous work in animation [2,3,4] and user controlled movement of 3D graphs [7], we can find no evidence of other research groups developing systems to aid comprehension by the automated regular movement of graph or similar data structures. Our paper at IV03 [1] introduced movement for the understanding of graphs. The initial study described in that paper showed some promising results, but the outcome was ambiguous.…”
Section: Introductionmentioning
confidence: 99%
“…Various kinds of graph movement are possible (see [1] for a further discussion), however in this paper we used circular motion in which the nodes are out of phase with each other. That is, each node moves in small, smooth, circles of the same size and speed, but with different nodes at different points on the circle so that the nodes move relatively to each other.…”
mentioning
confidence: 99%